Perkembangan Sistem Ekonomi di Indonesia - Susanto, Dedi; Amiruddin (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2025)
This study examines the development of Indonesia’s economic system from the early independence period, the New Order era, to the Reform era, highlighting the dynamics of policy changes, challenges faced, and their implications for public welfare. In the early independence period, the economy was characterized by etatism, with the state acting as the main controller; however, weak infrastructure and political instability hindered its effectiveness. The New Order era was marked by rapid economic growth through a mixed economic model and industrialization, yet it was overshadowed by inequality, dependence on oil and foreign debt, as well as corruption, collusion, and nepotism (KKN). Meanwhile, the Reform era introduced market liberalization and global openness, although issues of equity, economic sovereignty, and foreign capital dominance remained unresolved. Using a descriptive qualitative approach, this study emphasizes that the success of Indonesia’s economic development depends on balancing market efficiency, political stability, good governance, and the implementation of social justice principles in accordance with Article 33 of the 1945 Constitution.